If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7.2x + 2 = 6.2x Reorder the terms: 2 + 7.2x = 6.2x Solving 2 + 7.2x = 6.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.2x' to each side of the equation. 2 + 7.2x + -6.2x = 6.2x + -6.2x Combine like terms: 7.2x + -6.2x = 1x 2 + 1x = 6.2x + -6.2x Combine like terms: 6.2x + -6.2x = 0.0 2 + 1x = 0.0 Add '-2' to each side of the equation. 2 + -2 + 1x = 0.0 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = 0.0 + -2 1x = 0.0 + -2 Combine like terms: 0.0 + -2 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 15f=k(k-f)+7+8f | | 1x+45=2x-2 | | (40x+16/6)/(20x+8/6x) | | 88=n+81 | | u+32=99 | | 0.091=1-z | | -20p+10=-19p-19 | | y^8*y^15= | | 7q=84 | | 4.7d=6.11 | | -20p+10p=-19p-19 | | 5.6-0.32s=1.12 | | 16.15=w+3 | | y+3.33=14.33 | | 208-3x=(x+1)+(x+2)+(x+3)-50 | | 10*0.32-5.6=1.12 | | -4+4=-29 | | 7=3.14+x | | 7=3.14 | | 7x^3+20x^2-32x=0 | | 208-3x=(x+1)+(x+2)+(x+3)+(x+4)-50 | | 8x+8=5x+5 | | 12x+8=90 | | 3+x=3-x | | 9x=15+3x | | 3y+15=4y-20 | | 2x+3(4x+2)=34 | | 28=6g-8 | | 2x-20=x/2+10 | | 48x^3-12x^2-6x=0 | | 54-2x=10x-18 | | 7-(2x-8)=5-3x |